(untitled) (Construction Economics and Building, 2016)
This study sets out to investigate the relationships between the organisational life cycles, business orientation and performances of architectural firms, which often start with just the principal and little capital. In the study, the organisational life cycles stages of the firms were identified, and the way that business orientation emphasis changes with the firms’ life cycles were investigated. In addition, the business orientation dimensions that predict the architectural firms’ performance at each life cycle stage were identified. The study was carried out using data collected through self-administered questionnaires from architectural firms in Nigeria. The organisational life cycle stages of the firms were identified using cluster analysis, and the predictors of performances were identified using regression analysis. The results of the study show that only focus on prominence varied significantly with the organisational life cycles of the firms. Another important finding of the study is that market orientation led to better performance at some organisational life-cycle stages, while profit orientation led to better performance at some other stages. It was recommended that firms should choose business strategies that take into consideration their organisational life cycle stages to enhance their performances.